KETELADANAN GURU DALAM PROSES PENDIDIKAN DI SEKOLAH - Karso, Karso (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study describes the exemplary teacher who is very influential on the learning process of students of SDN 4 Pulau Rimau in Pulau Rimau sub-district, Banyuasin Regency, in: (1) exemplary teachers, (2) understanding of teachers (3) understanding of exemplary teachers and, (4) types kind of exemplary teacher. This study used a qualitative approach with the type of case study at Rimau SDN 4 school. The research subjects were the Principal, Teachers, Education Personnel, and parents of students (school committees). The technique of collecting data uses observation and interview techniques, then the principal is oriented to supportive behavior, teacher behavior that has willingness, sincerity / sincerity, and seriousness in carrying out the task because the teacher is a figure who is cared for and imitated, disciplined education personnel, all of that make students at SDN 4 Rimau Island follow the example.